Effect of Different Level of Lemon Extract on Quality and Shelf Life of Chicken Meatballs During Frozen Storage - Disha, MNA; Hossain, MA; Kamal, MT; Rahman, MM; Hashem, MA (SAARC Journal of Agriculture, 2021)
The aim of the current study was to find out the effect of adding different levels of lemon extract to the chicken meatballs. Fresh lemon extract was incorporated into freshly prepared meatball and compared with 0.01 % beta hydroxyl toluene (BHT) and control (without antioxidant). For this purpose, chicken meatball samples were divided into four treatment groups; viz. T0 (Control), T1 (0.01% BHT), T2 (0.5 % lemon extract) and T3 (1 % lemon extract). The study was conducted in completely randomized factorial design. The samples were analyzed for determination of sensory, proximate components, physicochemical, biochemical and microbiological qualities at 0, 30th and 90th days of preservation. Color, flavor, Juiciness, tenderness and overall acceptability increased significantly (p<0.05) among different treatment groups than control and BHT group but decreased at different days of intervals. Dry matter (DM) content decreased significantly (p<0.05) with different treatment levels than control and BHT group and increased with days of intervals. Crude protein (CP), ether extract (EE) and Ash of all treatments were decreased significantly (p<0.05) among different treatment groups. Raw pH, cooked pH and cooking loss were decreased significantly (p<0.05) with different treatment levels than control and BHT group and decreased with days of intervals. Free fatty acid (FFA), peroxide value (POV) and thiobarbituric acid reactive substances (TBARS) value were decreased significantly (p<0.05) with different treatment levels than that of control and BHT group and increased with days of intervals. Total viable count (TVC), total coli form count (TCC) and total yeast mould count (TYMC) decreased significantly (p<0.05) at different treatment levels than that of control and BHT group. Therefore, it can be concluded that 1 % lemon extract for formulation of value-added chicken meatballs was enriched source as natural antioxidant. SAARC J. Agri., 18(2): 139-156 (2020)